As elites organizacionais e o discurso da flexibilidade : uma análise sob a perspectiva das relações de poder - Sanchez, José Paulo de Angelo (Universidade Federal de São Carlos, 2015)
Generally speaking, the evolution of organizational behavior has been analyzed almost exclusively from the economic and technological transformations point of view. According to this perspective, firms are transformed by market forces as they struggle to adapt to customers’ demands in order to become more competitive and to survive and thrive. This viewpoint neglects the influence of powerful interests institutionalized in society, which manifests themselves inside firms through the actuation of organizational elites. Based on the study of organizational elites and the power relations they establish we are able to achieve a better understanding of factors that determine organizational behavior. With the advent of continuous transformations to which companies have been submitted with the stated purpose of giving them greater flexibility in the face of increasingly competitive markets, the old static organizational structures began to give way to network organizations, more susceptible to restructuring in order to suit economic interests. This flexible organizational environment would require also flexible professionals, averse to excessive specialization, which could hinder them the freedom to move through the organizational network seeking for new opportunities. The changes associated with this flexibility discourse, in turn, may offer opportunities to favoring not declared interests of the organizational elites. In this sense, the subject of our study is how the flexibility discourse might be used instrumentally by organizational elites in their internal disputes for leading positions in companies. More to the point, the question that we propose to investigate is: ‘would it be possible to identify in the behavior of members of organizational elites some evidence of the usage of the flexibility discourse as a tool to compete for command positions within organizations?’ It is not our intention to answer that question categorically, but to advance in the understanding of this topic through a reflection based on theoretical and empirical evidence. In order to seek possible answers we have investigated the careers of business consultants who worked for a multinational consulting company operating in Brazil. We have found that having worked for a renowned business consulting company represents a significant shortcut for executive positions in organizations from several industries, especially if coupled with an MBA title by some prominent American or European business school. This can be taken as an evidence that the flexibility discourse is aligned to the interests of organizational elites, to the extent that it legitimizes their claims to rise to positions of power in organizations without going through the lengthy path required by the assimilation of specific knowledge of each type of activity or industry.
Keywords: Elites; Poder; Financeirização; Flexibilidade; Teoria das organizações; Power; Financialization; Flexibility; Organization Theory; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA ECONOMICA